Global Supply Chains: New Trends in the Context of the Coronavirus Pandemic - I. V. Boiko (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2021)
The article is dedicated to the new trends emerging in the global supply chain, related to the coronavirus pandemic COVID-19, substantially affected production, transportation and marketing of goods. The authors underline a high risks of initial chain location in China, which sporadically leads to a localization of production supply within national borders. This biase in the international logistics is rather long term than short term I terms of national sustainability. The authors underline the icreasing significance of risk reduction and supply chain reliability over minimization of cost in the logistical decision makings. The ambivalency in the trade of the pandemic emergency goods is analysed in a sense of providing specifically favourable terms for its sirculation among the countries on the one side and the national protection issued for such goods by the national governments, pursuing its sufficient provision on the domestic market on the other side.